Combined physical exercise and mindfulness therapy for psychophysiological and glycemic regulation in type 2 diabetes mellitus: A systematic review - Bangun, Henny Arwina; Girsang, Ermi; Siregar, Santy Deasy (Jurnal Kesmas Prima Indonesia, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder with substantial psychophysiological components. Integrated therapeutic approaches combining physical exercise and mindfulness practices may address both glycemic and psychological aspects, yet comprehensive evidence remains limited. This systematic review evaluated the effectiveness of combined physical exercise and mindfulness interventions on glycemic regulation and psychophysiological outcomes in patients with T2DM. A systematic search of PubMed, ScienceDirect, and Google Scholar identified experimental and quasi-experimental studies published between 2021 and 2025. Eligible studies included adult patients with T2DM who received combined physical exercise and mindfulness interventions. Outcomes assessed included glycemic control (HbA1c, fasting blood glucose) and psychophysiological parameters (stress, depression, quality of life). Narrative synthesis and comparison tables were used for qualitative analysis, and risk of bias was evaluated using the Cochrane RoB 2 tool and the Newcastle–Ottawa Scale. Five studies met the inclusion criteria (n = 386 participants). Combined interventions produced greater improvements than single-component or control conditions. Mean HbA1c reduction ranged from 0.7% to 1.1%, fasting blood glucose decreased by 12.5 to 23.07 mg/dL, and depression or stress scores declined by 20% to 45%. Additional benefits included better nerve conduction velocity, self-efficacy, medication adherence, and quality of life. Proposed mechanisms involved modulation of the hypothalamic-pituitary-adrenal axis, enhanced insulin sensitivity, and increased neuroplasticity. In conclusion, combined physical exercise and mindfulness interventions demonstrate superior effectiveness over single-modality or standard care approaches in improving glycemic control and psychophysiological well-being in T2DM. This integrated strategy represents a promising adjunct for T2DM management. Further randomized controlled trials with larger cohorts and extended follow-up are needed to substantiate clinical recommendations.